2013
DOI: 10.1016/j.orcp.2012.08.196
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of bariatric surgery vs. nonsurgical treatment of type 2 diabetes among severely obese adults

Abstract: Although all weight-loss approaches may improve insulin sensitivity in type 2 diabetes, bariatric surgery is believed to be the only reliable means of achieving diabetes remission. We conducted a retrospective cohort study to compare rates of diabetes remission, relapse and all-cause mortality among severely obese individuals with diabetes who underwent bariatric surgery versus nonsurgically treated individuals. Severely obese adults with uncontrolled or medication-controlled diabetes who underwent bariatric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 27 publications
5
37
0
Order By: Relevance
“…The magnitude of this effect varies by procedure (1). Our own work has suggested that there is a 5-year type 2 diabetes remission rate of 68% for Roux-en-Y gastric bypass (RYGB) (6,7). Despite the mounting evidence of the impact of bariatric surgery for patients with type 2 diabetes, studies have now begun to show that type 2 diabetes remission after bariatric surgery is often not durable, with rates of relapse as high as 43% after 15 years postsurgery (6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of this effect varies by procedure (1). Our own work has suggested that there is a 5-year type 2 diabetes remission rate of 68% for Roux-en-Y gastric bypass (RYGB) (6,7). Despite the mounting evidence of the impact of bariatric surgery for patients with type 2 diabetes, studies have now begun to show that type 2 diabetes remission after bariatric surgery is often not durable, with rates of relapse as high as 43% after 15 years postsurgery (6,8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent analysis of severely obese patients with diabetes, the adjusted probability of initial remission was 12-to 24-fold greater for the 1395 patients who had bariatric surgery than for the 62 322 who received usual medical care alone. 12 In a recently reported 6-year prospective study, remission of type 2 diabetes was significantly more common among patients who underwent Roux-en-Y gastric bypass (62%) than among severely obese patients with diabetes who initially sought but did not undergo bariatric surgery (6%) and those who never sought bariatric surgery (8%). 13 In another long-term analysis, remission of type 2 diabetes occurred in 68% of 4434 patients who had Rouxen-Y gastric bypass surgery, with a median duration of remission of 8 years.…”
mentioning
confidence: 97%
“…At 2 years the surgery subjects had significantly higher diabetes remission rates 73.7% compared to non surgical subjects with 6.9%. The surgical subjects also experienced lower relapse rates with no higher risk of death [28] . …”
mentioning
confidence: 85%
“…An editorial in the same edition by Zimmet et al [27] suggests that the bariatric surgery should not be seen as a last resort. More recently Arterburn et al [28] did a retrospective analysis to compare rates of diabetes remission, relapse and all cause mortality amongst severely obese adults with diabetes who underwent bariatric surgery vs non-surgical treated individuals. At 2 years the surgery subjects had significantly higher diabetes remission rates 73.7% compared to non surgical subjects with 6.9%.…”
mentioning
confidence: 99%